The effect of financial leverage, firm size and sales volatility on earning persistence (companies listed on the indonesia stock exchange) - Irwansyah Irwansyah; Yunita Fitria; Situmorang, Elga Oktaviola (INOVASI, 2023)
The study aims to analyze the effect of financial leverage, company size and sales volatility which is proxied by Agency Theory. The populations in this study are trading, service and investment companies listed on the Indonesia Stock Exchange in 2013-2017. The sampling technique uses purposive sampling with a total sample of 42 companies. The analysis of the study uses multiple regressions. We find several results showed that financial leverage and company size had a positive and significant effect on earnings persistence. Furthermore, sales volatility had a positive but not significant effect on earning persistence. Moreover, the study suggests adding other variables that are closely related to earnings persistence. It also suggests increasing the period of years, samples and objects of research in addition to trading companies, services and investments in order to obtain better results.